2019
DOI: 10.1126/science.aaw6699
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser welding of ceramics

Abstract: Welding of ceramics is a key missing component in modern manufacturing. Current methods cannot join ceramics in proximity to temperature-sensitive materials like polymers and electronic components. We introduce an ultrafast pulsed laser welding approach that relies on focusing light on interfaces to ensure an optical interaction volume in ceramics to stimulate nonlinear absorption processes, causing localized melting rather than ablation. The key is the interplay between linear and nonlinear optical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…have shown that 1‐ps pulses lead to more efficient welding than 230‐fs pulses. [ 12 ] Therefore, employing picosecond pulses should lead to significant—but not excessive—thermal effects, which are a prerequisite for laser welding. The Gaussian beam is focused through silicon at the interface with copper by means of an objective lens of numerical aperture NA = 0.26 mounted on a translation stage allowing its displacement along the optical axis z .…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that 1‐ps pulses lead to more efficient welding than 230‐fs pulses. [ 12 ] Therefore, employing picosecond pulses should lead to significant—but not excessive—thermal effects, which are a prerequisite for laser welding. The Gaussian beam is focused through silicon at the interface with copper by means of an objective lens of numerical aperture NA = 0.26 mounted on a translation stage allowing its displacement along the optical axis z .…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…[ 1–4 ] While ultrashort laser pulses represent an extraordinary tool for clean material removal with applications in material processing [ 5 ] or nanosurgery, [ 6 ] they are also attractive for additive manufacturing as they offer the possibility of joining a wide variety of materials that are impossible to bond using standard welding procedures. Nowadays, ultrafast laser welding can be successfully applied in configurations such as glass–metal, [ 7 ] glass–semiconductor, [ 8 ] glass–glass, [ 9,10 ] polymer–polymer, [ 11 ] and, more recently, ceramic–ceramic, [ 12 ] yielding MPa shear joining strengths. Given that this order of magnitude is similar or even higher than the one that can be obtained with traditional bonding methods (e.g., adhesive bonding), laser welding is an attractive alternative to these as it shows no aging or degasification problem.…”
Section: Introductionmentioning
confidence: 99%
“…Refractory oxide ceramics are usually produced by sintering, and applicationdriven incentives to study high temperature oxide melts have been largely limited to metallurgical slugs and glasses. The situation has changed with the application of additive manufacturing techniques to ceramic materials [2][3][4][5][6][7]. These techniques often involve laser melting, and their advance is hampered by a lack of data on oxide melts.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of laser science and technology, laser welding will become an important potential process for the joining of cemented carbides and steels. Ultrafast laser welding shows potential for achieving a lower heat input [111].…”
Section: Existing Main Issues Corresponding Solutions and Future Workmentioning
confidence: 99%